Enostaven način izpraznilne plevralne punkcije - Šegota, Nikša (Medicinski razgledi, 2001)
A simple method of thoracentesis with an ordinary 16 gauge intravenous needle has been described. The method is simple and inexpensive. 62 thoracenteses using this method were performed in outpatient and inpatient settings over oneyear. In most cases we obtained pleural punctate. Partial pneumothorax thatdid not require therapy has emerged as a complication only in two patients. Method safety allowed us to perform 25 % of thoracenteses on outpatient basis; after the procedure was performed chest x-ray was not routinely taken. The patients mostly endured the procedure without difficulties. In our country thoracenteses is often performed using expensive methods. We recommend the described method as a succesful, cheap and also a safe approach.
Keywords: Paracenteza; Pleural effusion; Diagnosis; Plevralni izliv; Paracentesis; plevra; diagnostika; therapy; zdravljenje